1992
DOI: 10.1073/pnas.89.8.3357
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human factor IX in mice after injection of genetically modified myoblasts.

Abstract: Hemophilia B is an X chromosome-linked recessive bleeding disorder. To develop a somatic gene therapy for this disease, we have examined whether mouse skeletal myoblasts can serve as efficient vehicles for systemic delivery of recombinant factor IX. When mouse myoblasts (C2C12) transduced with a Moloney murine leukemia virus-based vector containing the bacterial f-galactosidase gene were i 'ected into mouse skeletal muscles, they fused with the existing and regenerating myofibers and continued to express P-gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 22 publications
8
79
0
Order By: Relevance
“…Most muscledirected approaches for factor IX expression have involved the ex vivo transduction of myoblasts, which can be re-implanted and result in secretion of factor IX into the circulation. 5,6,17 These studies have gone far to establish that both myoblasts and mature myotubes are capable of the synthesis and required post-translational modifications of factor IX protein. In addition to ex vivo approaches, secretion of circulating proteins following direct muscle injection has also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most muscledirected approaches for factor IX expression have involved the ex vivo transduction of myoblasts, which can be re-implanted and result in secretion of factor IX into the circulation. 5,6,17 These studies have gone far to establish that both myoblasts and mature myotubes are capable of the synthesis and required post-translational modifications of factor IX protein. In addition to ex vivo approaches, secretion of circulating proteins following direct muscle injection has also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of myoblasts, in particular, not only to transcribe the factor IX transgene but also to perform the series of post-translational modifications required for functional activity has been established. 5,6 Genetically modified muscle cells are capable of producing a range of secreted proteins, including human growth hormone, erythropoietin, alpha-1-antitrypsin, and interleukin-10. [7][8][9][10] Recently, Xiao et al 3 demonstrated in vivo that mouse skeletal muscle, transduced with an E. coli ␤-galactosidase gene in a recombinant AAV (rAAV) vector, expressed the transgene for greater than 1.5 years in immunocompetent animals; Southern analysis of genomic DNA from transduced muscle suggested the expression persisted via high molecular weight viral genomes.…”
Section: Introductionmentioning
confidence: 99%
“…35 Retroviral vectors require dividing cells for nuclear entry, 36 thus cannot be used for efficient gene delivery to uninjured muscle. 37,38 Retroviral vectors have been used ex vivo to genetically modify dividing myoblasts, 39 followed by surgical implantation; however, the requirement for substantial tissue-culture manipulation and surgical expertise limit their ordinary use in man. Therefore, the development of a simple, safe and effective method of gene delivery to muscle resulting in long-term expression would be desirable.…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Skeletal muscle is capable of performing the necessary post-translational modifications required for functional FIX protein. 17 rAAV-2 targeting of skeletal muscle produces human FIX circulating levels up to 7% of normal human levels in immunodeficient mice. 18 The Chapel Hill strain hemophilia B canine is a well characterized animal model, 19,20 which has been used extensively for preclinical testing of anti-hemophilic products.…”
Section: Introductionmentioning
confidence: 99%